Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

L’apport de Maryvonne Kendergi à la SMCQ - Bail, Louise (Circuit : musiques contemporaines, 2017)
To measure Maryvonne Kendergi’s contributions to the smcq, it is necessary to revisit her career in Quebec, which was based on the solid academic and professional training she received at Parisian institutions from 1929 to 1952. Thereafter, in Montreal, she was hired by Radio-Canada for her exceptional voice, and in September 1956, she embarked on a brilliant radio career as a promoter of contemporary music. Kendergi gradually introduced the listening public to the arcana of the Montreal avant-garde. In this endeavour she was encouraged by Stockhausen’s arrival in Montreal in 1958, by composers’ efforts in organizing International Music Week in 1961, by the foundation of the smcq in 1966, and by the influence of the latter organization, particularly in its collaboration with the Université de Montréal in establishing the Musialogues in 1969. The role of Kendergi’s exceptional skills in broadening the influence of the smcq is explored in this article.
Keywords: Maryvonne Kendergi; Musialogues; Société de musique contemporaine du Québec (smcq); animatrice; host; music journalist; musicographe de radio